Counseling and Hand Washing Gymnastic As an Effort to Prevent COVID-19: Penyuluhan dan Senam Cuci Tangan Pakai Sabun sebagai Upaya Pencegahan COVID-19 - Christine Christine; Herlina Susanto Sunuh; Fellysca Veronica Margareth Politon (Poltekkes Kemenkes Palu, 2022)
One of the standard recommendations to prevent the spread of infections, including COVID-19, is through regular hand washing. Transmission of the COVID-19 virus can occur when someone touches an item that may have been contaminated by other people's droplets. However, there were still 24,62% of Indonesian people do not obey to wash their hands properly. During the COVID-19 pandemic, washing hands with soap at school is very important to prevent the transmission of COVID-19. The purpose of this activity was to improve student behavior in washing hands with soap properly. This activity was carried out by a team of lecturers and students of the D3 Sanitation Study Program, Poltekkes, the Ministry of Health, Palu together with SD Inpres 2 Parigimpuu. The method of activity, namely counseling, simulation, and demonstration through gymnastics for the students of SD Inpres 2 Parigimpuu. As a result of this activity, students knew how to wash their hands with soap correctly and are able to practice it.